Implementing a typed assembly language and its machine model - Medel, Ricardo (2002)
We describe the implementation of a first-order linearly typed assembly language, HBAL, that allows the safe reuse of heap space for elements of different types Linear typing ensures the single pointer property, disallowing aliasing, but allowing safe in-place-update compilation of a functional programming language. HBAL was designed as a target low-level language for Hofmann’s LFPL programs [5] that run in a bounded amount of heap space